Development of Digital Marketing Media and Product Optimization in Social Forestry Business Group Commodities in Kemantan Village: Pengembangan Media Digital Marketing dan Pengoptimalan Produk Pada Komoditas Kelompok Usaha Perhutanan Sosial Desa Kemantan - Urdana Chesta Adabi Purwanto; Kustini (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2024)
Social Forestry Business Group (KUPS) is an idea designed by the government to optimize community-based forest management in order to improve economic welfare and maintain environmental sustainability. KUPS can be called the same as MSMEs, but KUPS is under the auspices of social forestry. With the development of digital technology, online marketing is the most effective place to buy and sell. At KUPS Kemantan Village, business actors still sell forest commodity products traditionally and most of them are still semi-finished products whose value cannot be fully utilized. By utilizing digital marketing, it is hoped that it can increase sales, welfare, and increase the selling value of commodity products.